Vertical Stratification of Peat Pore Water Dissolved Organic Matter Composition in a Peat Bog in Northern Minnesota. Issue 2 (21st February 2018) - Tfaily, Malak M.; Wilson, Rachel M.; Cooper, William T.; Kostka, Joel E.; Hanson, Paul; Chanton, Jeffrey P.
Abstract: We characterized dissolved organic matter (DOM) composition throughout the peat column at the Marcell S1 forested bog in northern Minnesota and tested the hypothesis that redox oscillations associated with cycles of wetting and drying at the surface of the fluctuating water table correlate with increased carbon, sulfur, and nitrogen turn over. We found significant vertical stratification of DOM molecular composition and excitation‐emission matrix parallel factor analysis components within the peat column. In particular, the intermediate depth zone ( 50 cm) was identified as a zone where maximum decomposition and turnover is taking place. Surface DOM was dominated by inputs from surface vegetation. The intermediate depth zone was an area of high organic matter reactivity and increased microbial activity with diagenetic formation of many unique compounds, among them polycyclic aromatic compounds that contain both nitrogen and sulfur heteroatoms. These compounds have been previously observed in coal‐derived compounds and were assumed to be responsible for coal's biological activity. Biological processes triggered by redox oscillations taking place at the intermediate depth zone of the peat profile at the S1 bog are assumed to be responsible for the formation of these heteroatomic PACs in this system. Alternatively, these compounds could stem from black carbon and nitrogen derived from fires that have occurred at the site in the past. Surface and deep DOM exhibited more similar characteristics, compared to the intermediate depth zone, with the deep layer exhibiting greater input of microbially degraded organic matter than the surface suggesting that the entire peat profile consists of similar parent material at different degrees of decomposition and that lateral and vertical advection of pore water from the surface to the deeper horizons is responsible for such similarities. Our findings suggest that molecular composition of DOM in peatland pore water is dynamic and is a function of ecosystem activity, water table, redox oscillation, and pore water advection. Plain Language Summary: We found strong vertical stratification in dissolved organic matter molecular composition and optical properties within the peat column at the S1 bog. Surface samples were dominated by inputs from surface vegetation. The intermediate depth ( 50 cm) was an area of high reactivity and increased microbial activity with diagenetic formation of many unique compounds such as polycyclic aromatic compounds (PACs) that contain both nitrogen and sulfur heteroatoms. These compounds were previously observed in coal‐derived products and were assumed to be responsible for coal's biological activity. Biological processes taking place at the intermediate depth zone of the peat profile at the S1 bog are assumed to be responsible for the formation of these heteroatomic PACs in our system. Conversely, these compounds might stem from black carbon and nitrogen from potential fires that occurred at the site in the past. Key Points: DOM composition was vertically stratified with depth Microbial activity increased at the intermediate depth Our radiocarbon data suggested vertical/lateral advection with depth